Dead-reckoning-based indoor localization with wi-fi infrastructure support - Guo, Jie (2014)
In this project, a Wi-Fi Correction Scheme is proposed so the SparseTrack System is modified. The modified SparseTrack System consists of two sub-systems: the Dead-Reckoning Sub-System and the Ranging Sub-System. The Dead-Reckoning Sub-